Causes of fatal construction accidents in Malaysia - Abdul Rahim, A. H.; M. R. A., Noor Azmi; Eeydzah, Aminudin; Putra Jaya, Ramadhansyah; R., Zakaria; A. M. M., Zawawi; Khairulzan, Yahya; Zaiton, Haron; R., Yunus; C. C., Saar (IOP Publishing, 2019)
Malaysia has moved fast to keep pace with the changes of times as the country aspires to achieve strong economic growth and to chart its course as a developed nation by the year 2020. The construction industry is one of the important sectors for nations to develop our country's economy and thus able to improve our competitiveness. However, in line with the positive growth of the economy, the construction sector also contributes to the high accident fatality rate. Construction workers are often exposed to various inherent risks associated with working conditions on construction sites. Although various approaches have been implemented in order to prevent accidents, the statistic indicates further improvement need to be taken fast. The objective of the study is to analyse the statistics and causes of fatal accidents at construction sites in Malaysia. The study focuses on 129 fatal construction accident cases based on database and document kept by the Malaysian authority, such as Department of Occupational Safety and Health (DOSH) and Social Security Organisation (SOCSO). The collected data were analyzed using frequency analysis and content analysis. The analysis shows that the number of fatal accidents is increasing every year. In the last five years, statistic from SOCSO and DOSH has shown an increasing number of fatal accident cases for about 231.9% and 125.8% respectively. The top three causes of fatal construction accidents are unsafe methods, the unique nature of industry and job site conditions. Whereas, the leading sub-causes are work at high elevation, incorrect or no work procedure and failure of structure.